2017
DOI: 10.3892/or.2017.6048
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-induced inhibition of the endocannabinoid system in glioblastoma cells

Abstract: The endocannabinoid system plays an important role in the regulation of physiological and pathological conditions, including inflammation and cancer. Hypoxia is a fundamental phenomenon for the establishment and maintenance of the microenvironments in various physiological and pathological conditions. However, the influence of hypoxia on the endocannabinoid system is not fully understood. In the present study, we investigated the effects of hypoxia on the endocannabinoid system in malignant brain tumors. We su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 35 publications
1
9
0
Order By: Relevance
“…These results suggest that CB1 might not be committed to cell viability directly in U-87 cells. However, as shown in our previous study that hypoxia decreased the expression of CB1 in U-87 MG cells, the cannabinoid receptor agonist WIN 55,212-2 decreased glioblastoma cell viability, with the extent depending on the expression level of the CB1 receptor (5). In the present study, we showed that corticosterone downregulated the expression of CB1 and suppressed WIN 55,212-2-induced decrease in U-87 MG cell viability.…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…These results suggest that CB1 might not be committed to cell viability directly in U-87 cells. However, as shown in our previous study that hypoxia decreased the expression of CB1 in U-87 MG cells, the cannabinoid receptor agonist WIN 55,212-2 decreased glioblastoma cell viability, with the extent depending on the expression level of the CB1 receptor (5). In the present study, we showed that corticosterone downregulated the expression of CB1 and suppressed WIN 55,212-2-induced decrease in U-87 MG cell viability.…”
Section: Discussionsupporting
confidence: 77%
“…Interestingly, emotional and physical stressors release corticosteroids and, in turn, impair the endocannabinoid system (8). We previously showed that hypoxia aggravates cancer by inhibiting the endocannabinoid system in malignant glioblastoma cells (5). Thus, dysfunction of the endocannabinoid system by stress-released corticosteroids may lead to the development and progression of malignancies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the tumor microenvironment, hypoxia is known to upregulate the expression of cyclooxygenase-2 (COX-2) via hypoxia-inducible factor-1 (HIF-1) signaling ( Greenhough et al, 2009 ). COX-2 is one of the enzymes responsible for metabolism of ECs ( Sugimoto et al, 2017 ) with the main substrates being AEA and 2-AG ( Chiurchiu et al, 2015 ). Therefore, missing upregulation of ECs at Concordia (high altitude) might be due to hypoxia-induced upregulation of COX-2 (and possibly other enzymes) which in turn oxidizes ECs into compounds (e.g., prostaglandin-ethanolamides, hydroxy-AEAs) ( Chiurchiu et al, 2015 ) that were beyond the scope of our investigations.…”
Section: Discussionmentioning
confidence: 99%